Pemphigus Vulgaris with Solitary Toxic Thyroid Nodule - Mostafa Alfishawy; Karim Anwar; Amira Elbendary; Ahmed Daoud (Case Reports in Endocrinology)
Background. Pemphigus vulgaris is an autoimmune vesiculobullous disease, affecting the skin and mucous membranes. It is reported to be associated with other autoimmune diseases including autoimmune thyroid diseases. However we report herein a case of pemphigus vulgaris associated with autonomous toxic nodule. Case Presentation. A 51-year-old woman was evaluated for blisters and erosions that develop on her trunk, face, and extremities, with a five-year history of progressively enlarging neck mass, and a past medical history of pemphigus vulgaris seven years ago. The condition was associated with palpitation, dyspnea, and heat intolerance. Thyroid function tests and thyroid scan were compatible with the diagnosis of thyrotoxicosis due to autonomous toxic nodule. Exacerbation of pemphigus vulgaris was proved by skin biopsy from the patient which revealed histologic picture of pemphigus vulgaris. Conclusion. Autoimmune thyroid diseases are reported to associate pemphigus vulgaris. To our knowledge, this case is the first in the English literature to report association between pemphigus vulgaris and autonomous toxic nodule and highlights the possibility of occurrence of pemphigus vulgaris with a nonautoimmune thyroid disease raising the question: is it just a coincidence or is there an explanation for the occurrence of both conditions together?